Attentional development can help us understand the inattentional blindness effect in visual search - Gil-Gómez de Liaño, Beatriz; Castelletti, Chiara; Perez-Hernandez, Elena; Quirós-Godoy, María; Wolfe, Jeremy M. (Frontiers in Cognition, 2023)
Inattentional Blindness (IB) is the failure to notice an unexpected, usually salient stimulus while immersed in a different, often demanding attentional task. More than just a laboratory curiosity, IB is an important phenomenon to understand because it may be related to real-world errors such as missed “incidental findings” in medical image or security searches. Interest in individual differences in susceptibility to IB has produced a number of studies showing inconclusive results. Here, we tested IB in a sample of 277 participants, 4-25 years old performing a visual search task. On two critical trials, an unexpected letter and an unexpected word were presented among photorealistic objects. There was a clear age effect with younger individuals showing higher IB levels. IB correlated with attentional control in visual search and with Continuous Performance Test-CPT for d-prime, response times and attentional shifting measures. These effects disappeared if age was controlled. There were no general effects of intelligence (IQ; RIST) or gender. Younger observers showed a negative correlation of IB for the word with the verbal components of the RIST IQ-proxy (no effect for the letter). These results support a relationship between IB and cognitive-developmental changes, showing that maturation of attention and executive processes can help us understanding the intriguing phenomenon of (sometimes) missing what is in front of our eyes.